Analysing the effects of 3D printing defects and surface roughness on the properties of acoustic materials - Ciochon, Agnieszka Helena (Trinity College Dublin. School of Engineering. Discipline of Mechanical & Manuf. Eng, 2023)
The principal aim of the research reported in this thesis was to investigate the influence of additive manufacturing on the acoustic performance of 3D printed periodic materials. First, a benchmark material design was manufactured using three different 3D printing technologies. The quality of produced samples was inspected using several non-destructive testing techniques. Realistic computational geometries of samples produced via extrusion-based additive manufacturing were created based on surface profiles obtained with confocal microscopy. This data was then used to update an existing numerical model, which initially assumed a smooth surface finish of the benchmark unit cell. The rough computational geometries were proposed as an enhanced unit cell design and produced using photopolymerisation-based additive manufacturing technology in the next step. Finally, a new 3D printed acoustic-material solution was also designed based on the benchmark unit cell. This acoustic material solution was produced via extrusion-based additive manufacturing and inserted into the interior of a commercial building acoustics silencer for performance enhancements. The presently-reported research confirmed that additive manufacturing has an acoustic impact (increase of magnitude of absorption, operating frequency shift) on the performance of designed material due to the distortion of idealised, smooth computational geometry caused by layer-by-layer fabrication and additional 3D printing defects. Surface roughness resulting from the staircase effect is partially responsible for the mismatch between numerical predictions and experimental results. It can be used for acoustic gains by enhancing the smooth, benchmark design with additional artificial roughness applied to its surfaces. This thesis has also shown that acoustic materials can be designed for target frequencies of interest to enhance the broadband behaviour of foam liners and improve the acoustic performance of the off-shelf components.
APPROVED
Keywords: additive manufacturing; 3D printing; 3D printing defects; surface roughness; acoustic materials